Assembly and Activation of the Intrinsic Fibrinolytic Pathway on the Surface of Human Endothelial Cells in Culture - Lenich, Catherine; Pannell, Ralph; Gurewich, Victor (Thrombosis and Haemostasis, 1995)
Factor XII has long been implicated in the intrinsic pathway of fibrinolysis, but the mechanism by which it triggers plasminogen activation and targets fibrinolysis has not been established. In the present study, the assembly and function of activated Factor XII (F.XIIa), prourokinase (pro-u-PA), high molecular weight kininogen (H-kininogen), and prekallikrein on human umbilical vein endothelial cells (HUVEC) was investigated. 125I-prekallikrein was shown to bind to HUVEC via receptor-bound H-kininogen in the presence of 50 μM ZnCl2. After the addition of F.XIIa, 78% of the 125I-prekallikrein initially bound to HUVEC was converted to 125I-kallikrein. However, only 6% of the HUVEC-bound 125I-pro-u-PA was thereby activated. This discrepancy was shown to be related to rapid dissociation (>50% within 15 min) of prekallikrein/kallikrein, but not pro-u-PA, from HUVEC. Increasing the level of cell-bound kallikrein increased the portion of cell-bound pro-u-PA activated, indicating that their co-localization was important for this pathway. Finally, F.XIIa was shown to trigger plasminogen activation on HUVEC via this pathway. This assembly of reactants on the endothelium suggests a mechanism whereby local fibrinolysis may be triggered by blood coagulation.